Application of four-functional alicyclic epoxy compound in preparation of solder resist dry film
By using the high functionality and high steric resistance characteristics of the tetrafunctional alicyclic epoxy compound, the problem of low thermal curing of multi-functional alicyclic epoxy resin in the prior art is solved, and a solder-resistant dry film with high crosslink density is realized, which improves its thermal and mechanical properties, and is suitable for packaging and protection of various electronic devices.
Patent Information
- Application Number
- CN202411970915.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The polyfunctional alicyclic epoxy resins in the prior art have low functionality or large epoxy steric resistance, resulting in low thermal curing degree, making it difficult to meet the thermal performance and mechanical properties requirements of solder-resistant dry films in the PCB manufacturing process.
The four-functional alicyclic epoxy compound is used. Its structure has four epoxy groups and alicyclic structure, which has high functionality and has a small impact on the epoxy group. It is easy to react with the carboxyl group of alkali-soluble groups to form a network structure with high cross-link density and improve the degree of thermal curing.
Through the application of tetrafunctional alicyclic epoxy compounds, the solder-resistant dry film prepared has high thermal curing degree and has excellent chemical resistance, mechanical properties and electrical properties. It is suitable for UV packaging and coating protection for optical display, electronic manufacturing, flat panel and flexible display equipment.
Smart Images

Figure CN119758667A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocurable materials, and in particular relates to the application of a tetrafunctional alicyclic epoxy compound in the preparation of a solder resist dry film. Background Art
[0002] Solder mask dry film is an important component of printed circuit boards. It is attached to the circuit substrate to form a solder mask layer, isolating the circuit lines on the printed circuit board, thereby preventing short circuits and ensuring the integrity of electrical connections. The solder mask dry film should be attached to the PCB board, and then exposed, developed and post-baked through a mask with a pattern. The purpose of post-baking thermal curing is to further cross-link the carboxyl group and epoxy group in the photocured dry film, improve the thermal and mechanical properties of the solder mask dry film, and enable it to withstand various harsh conditions in the PCB manufacturing process, including thermal cycling, chemical exposure and mechanical stress.
[0003] Solder resist dry film generally contains alkali-soluble photosensitive resin and thermosetting resin. The double bonds of alkali-soluble photosensitive resin are cross-linked during photocuring, and the carboxyl group reacts with the epoxy group of the thermosetting resin. Traditional thermosetting resins are generally bisphenol A type epoxy resins, novolac epoxy resins, biphenyl type and epoxy resins containing naphthalene ring structures, but their reaction activity with carboxyl groups on the resin is low, and the cross-linking reaction is slow and incomplete. The reaction activation energy of alicyclic epoxy resins with carboxyl groups is low, and it is easier to react with carboxyl groups. At the same time, the rigid structure of the alicyclic and the high cross-linking density of the cured product make it have good bonding strength to different substrates, high heat deformation temperature, excellent chemical resistance, and mechanical and electrical properties. However, the multi-functional alicyclic epoxy resins in the prior art have low functionality or large epoxy group steric hindrance, resulting in a low degree of thermosetting. Therefore, it is necessary to find a multi-functional alicyclic epoxy resin that can be used to prepare solder resist dry film. Summary of the invention
[0004] The first object of the present invention is to provide an application of a tetrafunctional alicyclic epoxy compound in the preparation of a solder resist dry film, so as to solve at least one of the above-mentioned technical problems.
[0005] The first aspect of the present invention provides the use of a tetrafunctional alicyclic epoxy compound in the preparation of a solder resist dry film, wherein the structural formula of the tetrafunctional alicyclic epoxy compound is shown in formula (I):
[0006]
[0007] The tetrafunctional alicyclic epoxy compound of the present invention has an alicyclic ring and an epoxy group. When the epoxy group reacts with the carboxyl group, the functionality of the tetrafunctional alicyclic epoxy compound is 4, which is high in functionality. The structure of the tetrafunctional alicyclic epoxy compound makes the steric effect have a small effect on the epoxy group. Therefore, when the solder resist dry film is thermally cured, the epoxy group of the tetrafunctional alicyclic epoxy compound is easy to react with the carboxyl group of the alkali-soluble group, which is beneficial to the cross-linking of the resin during the thermal curing process. The degree of thermal curing is high, and the tetrafunctional alicyclic epoxy compound can be used to prepare the solder resist dry film. The tetrafunctional alicyclic epoxy compound reacts with the carboxyl group of the alkali-soluble resin during the thermal curing process of the solder resist dry film to form a complex network structure, which can improve the performance of the solder resist dry film.
[0008] In some embodiments, the solder resist dry film prepared from the tetrafunctional alicyclic epoxy compound is used for UV encapsulation and coating protection of at least one of optical display, electronic manufacturing, flat panel and flexible display devices. Specifically, the tetrafunctional alicyclic epoxy compound can be used as a solder resist dry film resin composition prepared from a thermosetting resin, and the solder resist dry film after curing can be used for UV encapsulation and coating protection of optical display, electronic manufacturing, flat panel and flexible display devices.
[0009] In some embodiments, the application of a tetrafunctional alicyclic epoxy compound in a solder resist dry film is the application of a tetrafunctional alicyclic epoxy compound in preparing a solder resist dry film resin composition. The solder resist dry film resin composition includes, by mass percentage, 45% to 55% alkali-soluble resin, 10% to 15% photosensitive monomer, 3% to 4% photoinitiator, 15% to 20% tetrafunctional alicyclic epoxy compound, 0.5% to 1.5% thermal curing catalyst, 0.5% to 1.5% defoaming agent, 0.5% to 1.5% leveling agent and 15 to 20% solvent.
[0010] The solder resist dry film resin composition of the present invention is subjected to the preparation of a photosensitive dry film, film lamination, exposure, development, and drying to obtain a solder resist dry film. After multiple performance tests, it is found that after the solder resist dry film resin composition of the present invention is cured into a solder resist dry film, the solder resist dry film has good sensitivity, resolution, and mechanical properties, and also has good flexibility and hardness.
[0011] In some embodiments, the photosensitive monomer is pentaerythritol triacrylate, the photoinitiator is diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO), the thermal curing catalyst is 2-methylimidazole, the leveling agent is polyacrylate, the defoamer is a silane copolymer defoamer, and the solvent is acetone.
[0012] In some embodiments, the molecular structure of the alkali-soluble resin contains at least one of a carboxyl group and a sulfonic acid group, the weight average molecular weight of the alkali-soluble resin is 6000 to 9000, and the acid value of the alkali-soluble resin is 40 to 120 mgKOH / g.
[0013] In some embodiments, the alkali-soluble resin can be prepared by the following steps: self-polymerization of glycidyl methacrylate, adding acrylic acid and epoxy to graft the acrylic acid structure, adding succinic anhydride to connect the carboxyl group at the end. According to the mass ratio, glycidyl methacrylate: acrylic acid: succinic anhydride = 100:50:7, and the solvent is propylene glycol monomethyl ether acetate.
[0014] In some embodiments, the method for using the solder resist dry film resin composition comprises the following steps:
[0015] Using a coating machine to coat the solder resist dry film resin composition on the surface of a PET support film with a thickness of 20 to 30 μm to obtain a photosensitive layer with a thickness of 20 to 30 μm, and covering the surface of the photosensitive layer with a PE protective film with a thickness of 20 to 30 μm;
[0016] The PE protective film is peeled off, and the solder resist dry film resin composition is attached to the surface of the electronic component. After baking at 90-110° C. for 3-10 minutes, it is allowed to stand for 10-20 minutes. Then, the circuit board is exposed with a laser having a wavelength of 300-400 nm, and then it is allowed to stand for 15-30 minutes. The PET supporting film is peeled off, the electronic component is developed, and then the electronic component is washed and dried to obtain the solder resist dry film attached to the electronic component.
[0017] In some embodiments, the method for preparing a tetrafunctional alicyclic epoxy compound comprises the following steps:
[0018] S1, pentaerythritol, 3-cyclohexene-1-carboxylic acid, a catalyst and an organic solvent are mixed to obtain a solid-liquid mixture, a condensing agent is dissolved in an organic solvent to obtain a first mixed solution, the first mixed solution is added dropwise to the solid-liquid mixture and stirred until the solid in the solid-liquid mixture is dissolved in the organic solvent, the mixture is reacted for 16 to 24 hours, the reaction system after the reaction is washed and dried to obtain an organic phase, the organic phase is then subjected to reduced pressure distillation, and the residue of the organic phase after the reduced pressure distillation is crystallized to obtain pentaerythritol tetracyclohexene formate;
[0019] S2. Dissolve pentaerythritol tetracyclohexene carboxylate in an organic solvent to obtain a second mixed solution, dissolve meta-chloroperbenzoic acid in an organic solvent to obtain a third mixed solution, then dropwise add the third mixed solution to the second mixed solution under ice bath conditions, stir and react for 16 to 24 hours, filter, purify the filtered filtrate to obtain an organic phase, and crystallize to obtain.
[0020] Among them, the catalyst can be selected from at least one of 4-dimethylaminopyridine (DMAP), 1-hydroxybenzotriazole (HOBt), and 4-pyrrolidinopyridine (4-PPY), and the condensing agent can be selected from at least one of N,N-dicyclohexylcarbodiimide (DCC), N,N-diisopropylcarbodiimide (DIC), and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDCI).
[0021] The preparation method of the tetrafunctional alicyclic epoxy compound of the present invention comprises the following steps: firstly, pentaerythritol and 3-cyclohexene-1-carboxylic acid are subjected to a Steglich esterification reaction in an organic solvent to prepare pentaerythritol tetracyclohexene carboxylate, and then the pentaerythritol tetracyclohexene carboxylate is epoxidized by m-chloroperbenzoic acid to obtain the tetrafunctional alicyclic epoxy compound.
[0022] In some embodiments, the molar ratio of pentaerythritol, 3-cyclohexene-1-carboxylic acid, catalyst and condensing agent is 1:(4-4.12):(1-1.10):(4-4.10).
[0023] In some embodiments, the amount of the catalyst used may be 8-10% of the total mass of pentaerythritol, 3-cyclohexene-1-carboxylic acid and the condensing agent.
[0024] In some embodiments, the amount of the catalyst used may be 8-9% of the total mass of pentaerythritol, 3-cyclohexene-1-carboxylic acid and the condensing agent.
[0025] In some embodiments, the amount of the catalyst used may be 8.5% of the total mass of pentaerythritol, 3-cyclohexene-1-carboxylic acid and the condensing agent.
[0026] In some embodiments, the organic solvent may be selected from at least one of tetrahydrofuran and dichloromethane.
[0027] In some embodiments, in step S1, the amount of the organic solvent used may be 4 to 6 times the total mass of pentaerythritol, 3-cyclohexene-1-carboxylic acid and the condensation agent.
[0028] In some embodiments, in the first mixed liquid, the volume of the organic solvent required to dissolve the condensing agent may be 350-450 mL.
[0029] It should be noted that in the present application, the purpose of adding an organic solvent to the solid-liquid mixture and the first mixed liquid is to dissolve pentaerythritol and the condensation agent in the organic solvent. The organic solvent does not participate in the reaction. Therefore, the amount of the above-mentioned organic solvent is only one of the options and cannot be used as a limitation of the present application.
[0030] In some embodiments, in step S2, the amount of the organic solvent used can be 10 times the mass of m-chloroperbenzoic acid.
[0031] In some embodiments, in the second mixed solution, the volume of the organic solvent required to dissolve pentaerythritol tetracyclohexene carboxylate may be 50-70 mL.
[0032] In some embodiments, in the third mixed liquid, the volume of the organic solvent required to dissolve meta-chloroperbenzoic acid may be 180-220 mL.
[0033] It should be noted that, in the present application, the purpose of using an organic solvent in the second mixed liquid and the third mixed liquid is to dissolve meta-chloroperbenzoic acid, and the amount of the above-mentioned organic solvent is only one of the options and cannot be used as a limitation of the present application.
[0034] In some embodiments, the molar ratio of pentaerythritol tetracyclohexene carboxylate to meta-chloroperbenzoic acid may be 1:(4-4.10).
[0035] In some embodiments, in step S1, the stirring and reaction time may be 18 hours.
[0036] In some embodiments, in step S1, the washing treatment method can be to transfer the reaction system after the reaction to a separatory funnel, first wash it 3 times with a hydrochloric acid solution with a mass fraction of 1%, then wash it 3 times with a saturated sodium bicarbonate solution, and finally wash it 3 times with a saturated sodium chloride solution, and separate the liquids to obtain a lower organic phase. Specifically, hydrochloric acid and the catalyst can be combined into a soluble salt that can be dissolved in water, and the excess catalyst in the reaction system is removed after washing; the saturated sodium bicarbonate solution is used to remove organic acids and hydrochloric acid, and adjust the pH of the reaction system to neutral; the saturated sodium chloride solution is used to remove water-soluble impurities in the organic phase.
[0037] In other embodiments, in step S1, the washing treatment method can be to transfer the reaction system after the reaction to a separatory funnel, wash it three times with a 1% hydrochloric acid solution, and then wash it three times with a saturated sodium chloride solution, and separate the liquids to obtain a lower organic phase.
[0038] In other embodiments, in step S1, the washing treatment method can be to transfer the reaction system after the reaction to a separatory funnel, wash the organic phase three times with a hydrochloric acid solution with a mass fraction of 1%, and separate the liquids to obtain a lower organic phase.
[0039] In some embodiments, in step S1, the drying treatment method may be to add a solid desiccant to the reaction system after washing, and filter and retain the organic phase obtained after filtration.
[0040] In some embodiments, the solid desiccant may be selected from at least one of anhydrous sodium sulfate or anhydrous magnesium sulfate.
[0041] In some embodiments, in step S1, the conditions for the reduced pressure distillation may be to distill the filtered organic phase under reduced pressure at a vacuum degree of -0.098 MPa and a water bath temperature of 30 to 40° C. for 1 to 3 hours.
[0042] In some embodiments, in step S2, the purification treatment method can be, first, add a saturated sodium sulfite solution to the filtrate, then wash the filtrate 3 times with a saturated sodium bicarbonate solution and a saturated sodium chloride solution respectively, separate the liquid to obtain a lower organic phase, add a solid desiccant to the washed organic phase, filter, and then remove the organic solvent in the organic phase by reduced pressure distillation. Specifically, the saturated sodium sulfite solution is used to remove excess meta-chloroperbenzoic acid, the saturated sodium bicarbonate solution is used to remove acidic impurities in the reaction system and adjust the pH of the reaction system to neutral, and the saturated sodium chloride solution is used in the reaction system to reduce the solubility of salt in the organic phase, so as to facilitate the removal of salt in the organic phase in the subsequent liquid separation.
[0043] In some embodiments, in step S2, the conditions for removing the organic solvent in the organic phase by reduced pressure distillation may be to distill the filtered organic phase under reduced pressure at a vacuum degree of -0.098 MPa and a water bath temperature of 30 to 40° C. for 1 to 3 hours.
[0044] In some embodiments, in step S2, the stirring and reaction time may be 18 hours.
[0045] In some embodiments, in step S2, the purification treatment method may be to further purify by column chromatography after reduced pressure distillation.
[0046] In some embodiments, the eluent used for column chromatography can be a mixture of petroleum ether and ethyl acetate, and the chromatography column used for column chromatography can be a silica gel column. The volume ratio of petroleum ether to ethyl acetate in the mixture can be (6-9):1.
[0047] The beneficial effects of the present invention are:
[0048] The present invention uses a tetrafunctional alicyclic epoxy compound as a raw material for a solder resist dry film, and utilizes the characteristics of the tetrafunctional alicyclic epoxy compound having four epoxy groups and an alicyclic structure. When the solder resist dry film is thermally cured, the epoxy group of the tetrafunctional alicyclic epoxy compound is easily reacted with the carboxyl group of the alkali-soluble group, and the thermal curing degree is high.
[0049] The tetrafunctional alicyclic epoxy compound of the present invention reacts with an alkali-soluble resin in a solder resist dry film to form a network structure, thereby improving the performance of the solder resist dry film. Performance tests have shown that the solder resist dry film prepared by using the tetrafunctional alicyclic epoxy compound in the solder resist dry film not only has good sensitivity, resolution and mechanical properties, but also has good flexibility and hardness, and can be coated on electronic components for optical display, electronic manufacturing, UV encapsulation and coating protection of flat panels and flexible display devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The infrared spectra of 3-cyclohexene-1-carboxylic acid, intermediates and products of Example 1 of the present invention are shown;
[0051] Figure 2 The hydrogen nuclear magnetic resonance spectra of the intermediate product and the product of Example 1 of the present invention are shown in FIG. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below in conjunction with the accompanying drawings, but the embodiments of the present invention are not limited thereto. The raw materials and reagents involved in the following examples can all be obtained from commercial channels.
[0053] Example 1
[0054] 6.8 g of pentaerythritol (0.05 mol), 25.23 g of 3-cyclohexene-1-carboxylic acid (0.2 mol), 6.13 g of DMAP (0.05 mol) and dichloromethane were added to a 500 mL three-necked flask in sequence to obtain a solid-liquid mixture, and 40.02 g of EDCI (0.2 mol) was dissolved in dichloromethane to obtain a first mixed solution; then the first mixed solution was added dropwise to the solid-liquid mixture, and after the addition was completed, the mixture was stirred at room temperature until the solid in the solid-liquid mixture was observed to be dissolved in the organic solution, and the reaction was carried out for 18 hours, and then the reaction system after the reaction was transferred to a separatory funnel, and dichloromethane was added to dilute it, and the mixture was first dissolved in 1% hydrochloric acid by mass, and then the mixture was stirred at room temperature until the solid in the solid-liquid mixture was observed to be dissolved in the organic solution. The mixture was washed three times with saturated sodium bicarbonate solution and saturated sodium chloride solution respectively, and the lower organic phase was obtained by separation; the organic phase was dried with anhydrous sodium sulfate and filtered to obtain the organic phase, and the dichloromethane and trace water in the organic phase were removed by reduced pressure distillation for 2 hours at a vacuum degree of -0.098MPa and a water bath temperature of 30-40°C, and then column chromatography was performed on a silica gel column (the eluent was a mixture of petroleum ether and ethyl acetate, and the volume ratio of the two was 7:1) to obtain a colorless viscous liquid, which was allowed to stand for crystallization to obtain a white crystalline intermediate product. The yield of the intermediate product was calculated to be 92.02%.
[0055] Add dichloromethane to a 500mL three-necked flask, then weigh 5.68g of the intermediate product (0.01mol) and add it to the three-necked flask. Slowly drop m-chloroperbenzoic acid (6.88g, 0.04mol) dissolved in dichloromethane into the three-necked flask under ice bath conditions, then heat to room temperature and stir to react for 18h, filter to remove the intermediate product, and remove excess m-chloroperbenzoic acid from the filtrate with a saturated sodium sulfite solution, then rinse with a saturated sodium bicarbonate solution and saturated brine. The organic phase was washed three times with the solution, and the lower organic phase was obtained by separation; the organic phase was dried with anhydrous magnesium sulfate and filtered to obtain the organic phase, and the dichloromethane and trace water in the organic phase were removed by reduced pressure distillation for 2 hours at a vacuum degree of -0.098MPa and a water bath temperature of 30-40°C, and then a silica gel column (the eluent was a mixture of petroleum ether and ethyl acetate, and the volume ratio of the two was 7:1) was used for column chromatography to obtain a colorless viscous liquid, and the colorless viscous liquid was allowed to stand for crystallization to obtain a white crystalline product. It was calculated that the yield of the intermediate product obtained by epoxidation was 91%.
[0056] The structures of the intermediate and product were confirmed by Fourier transform infrared spectroscopy (FT-IR) and hydrogen nuclear magnetic resonance (H-NMR) analysis. 3-cyclohexene-1-carboxylic acid, the intermediate and the product were analyzed by FT-IR. The results are as follows: Figure 1 As shown; the intermediate product and the product were analyzed by H-NMR, and the results are as follows Figure 2 shown.
[0057] from Figure 1 It can be seen that the infrared spectrum of 3-cyclohexene-1-carboxylic acid is between 3500 and 3000 cm -1 A strong and broad -COOH stretching vibration peak can be observed between the intermediate and the final product, while no -COOH stretching vibration peak is observed in the infrared spectra of the intermediate and the final product. -1 The stretching vibration peak is attributed to C=CH and is at 1739 cm -1 There is an obvious C=O characteristic absorption peak at 3500cm -1 There is no -OH stretching vibration peak belonging to pentaerythritol, indicating that the four hydroxyl groups of pentaerythritol and 3-cyclohexene-1-carboxylic acid successfully synthesized pentaerythritol tetracyclohexene carboxylate through esterification reaction. In the infrared spectrum of the product, 797cm -1 There is an absorption peak attributed to COC at 3031cm -1 The C=CH stretching vibration peak disappears, indicating that the double bond of pentaerythritol tetracyclohexene carboxylate disappears under the oxidation of m-chloroperbenzoic acid, generating a product with an epoxidized structure, indicating the successful synthesis of the product tetrafunctional alicyclic epoxy compound.
[0058] from Figure 2It can be seen that the chemical shift of the intermediate product (pentaerythritol tetracyclohexene carboxylate) is: 1H NMR (600MHz, Chloroform-d) δ5.68 (s, 8H), 4.18–4.12 (m, 8H), 2.62–2.55 (m, 4H), 2.28–2.20 (m, 8H), 2.13–2.05 (m, 8H), 2.01–1.94 (m, 4H), 1.68 (dddd, J=13.0, 11.2, 9.1, 6.8 Hz, 4H). The chemical shift of the product (tetrafunctional alicyclic epoxy compound) is: 1H NMR (600MHz, Chloroform-d) δ4.21–4.01 (m, 8H), 3.20 (ddd, J=57.2, 5.5, 3.2Hz, 8H), 2.58–2.47 (m, 2H), 2.32–1.53 (m, 26H). Comparing the H NMR spectra of the intermediate and the product, it can be found that the characteristic peak of the double bond on the six-membered ring of 3-cyclohexene-1-carboxylic acid at 5.68ppm in pentaerythritol tetracyclohexene carboxylate disappears in the spectrum of the tetrafunctional alicyclic epoxy compound, and two new characteristic peaks belonging to the epoxy group appear at 3.24-3.15ppm in the tetrafunctional alicyclic epoxy compound, further indicating the successful synthesis of the tetrafunctional alicyclic epoxy compound.
[0059] Example 2
[0060] This embodiment provides a method for preparing a tetrafunctional alicyclic epoxy compound, comprising the following steps:
[0061] 6.8 g of pentaerythritol (0.05 mol), 25.23 g of 3-cyclohexene-1-carboxylic acid (0.2 mol), 6.13 g of DMAP (0.05 mol) and dichloromethane were added to a 500 mL three-necked flask in sequence to obtain a solid-liquid mixture, and 40.03 g of EDCI (0.2 mol) was dissolved in dichloromethane to obtain a first mixed solution; then the first mixed solution was added dropwise to the solid-liquid mixture, and after the addition was completed, the mixture was stirred at room temperature until the solid in the solid-liquid mixture was observed to be dissolved in the organic solution, and the reaction was continued for 18 h, and then the reaction mixture was stirred for 18 h. The reaction system was transferred to a separatory funnel, washed three times with a hydrochloric acid solution having a mass fraction of 1%, separated to obtain a lower organic phase, dried with anhydrous sodium sulfate and filtered to obtain an organic phase, and distilled under reduced pressure for 2 hours at a vacuum degree of -0.098MPa and a water bath temperature of 30-40°C to remove dichloromethane and trace amounts of water in the organic phase, and then column chromatography was performed using a silica gel column (the eluent was a mixture of petroleum ether and ethyl acetate, the volume ratio of the two being 7:1) to obtain a colorless viscous liquid, which was allowed to stand for crystallization to obtain a white crystalline intermediate product. The intermediate product weighed 24.16g, and the yield of the intermediate product was calculated to be 85.07%.
[0062] First, add dichloromethane to a 500 ml three-necked flask, then weigh 5.68 g of the intermediate product (0.01 mol) and add it to the three-necked flask. Slowly drop m-chloroperbenzoic acid (83% activity, 8.28 g, 0.04 mol) dissolved in 250 mL of dichloromethane into the three-necked flask under ice bath conditions, then heat to room temperature and stir to react for 18 h, filter to remove the intermediate product, remove excess m-chloroperbenzoic acid from the filtered filtrate with a saturated sodium sulfite solution, and then add a saturated sodium bicarbonate solution. and saturated salt water solution for three times, and separated to obtain the lower organic phase; dried with anhydrous sodium sulfate and filtered to obtain the organic phase, and vacuum distilled for 2 hours at a vacuum degree of -0.098MPa and a water bath temperature of 30-40°C to remove dichloromethane and trace water in the organic phase, and then column chromatography was performed on a silica gel column (the eluent was a mixture of petroleum ether and ethyl acetate, and the volume ratio of the two was 7:1) to obtain a colorless viscous liquid, and the colorless viscous liquid was allowed to stand for crystallization to obtain a white crystalline product. The product weighed 5.69g, and the yield of the product obtained by epoxidation of the intermediate product was calculated to be 90.03%.
[0063] The structures of the intermediate product and the product were confirmed by Fourier transform infrared spectroscopy (FT-IR) and hydrogen nuclear magnetic resonance (H-NMR) analysis, respectively. The results were the same as those of Example 1, indicating that the intermediate product pentaerythritol tetracyclohexene carboxylate and the product tetrafunctional alicyclic epoxy compound were successfully synthesized.
[0064] The application of the tetrafunctional alicyclic epoxy compound of the present invention in the solder resist dry film is described in detail below. Specifically, the tetrafunctional alicyclic epoxy compound prepared in Example 1 and Example 2 is used to prepare the solder resist dry film resin composition.
[0065] In the application examples and comparative examples of the present invention, the alkali-soluble resin is an alkali-soluble resin synthesized with reference to Chinese patent CN118489087A, and its preparation method comprises the following steps:
[0066] Add 25g of glycidyl methacrylate and 53mL of propylene glycol monomethyl ether acetate to a three-necked flask, then add 17g of azobisisobutylnitrile, introduce nitrogen and heat to 80°C for reaction for 8h; add dropwise a mixed solution consisting of 13.3g of acrylic acid, 0.25g of triphenylphosphine, 5mg of hydroquinone and 3.25mL of propylene glycol monomethyl ether acetate to the three-necked flask, heat to 100°C for reaction for 16h; after the reaction, add 0.925g of succinic anhydride solution dissolved in 2.6mL of propylene glycol monomethyl ether acetate to the three-necked flask, cool to 65°C, and react for 6h to obtain.
[0067] The solid content, weight average molecular weight and acid value of the obtained alkali-soluble resin were measured respectively, wherein the solid content was measured by weighing a certain amount of sample, placing it in an oven at 120°C for 2 hours, and weighing the sample after cooling for 15 minutes. The weight average molecular weight was measured by GPC, and the acid value was measured by titration with a sodium hydroxide standard solution.
[0068] According to the test, the alkali-soluble resin used in the embodiment of the present invention has a solid content of 45%, a weight average molecular weight of 7000, and an acid value of 50 mgKOH / g.
[0069] It should be noted that the alkali-soluble resin can also be obtained from commercial channels, with a weight average molecular weight of 6000-9000, an acid value of 40-120 mgKOH / g, a solid content of 40-50%, and a molecular structure containing at least one of a carboxyl group and a sulfonic acid group.
[0070] Application Example 1
[0071] This application example provides an application of the tetrafunctional alicyclic epoxy compound prepared in Example 1 in preparing a solder resist dry film resin composition, comprising the following steps:
[0072] According to the formula of the solder resist dry film resin composition shown in Table 1, an alkali-soluble resin, a photosensitive monomer, a photoinitiator, the tetrafunctional alicyclic epoxy compound prepared in Example 1, a thermal curing catalyst, an additive and a solvent are uniformly mixed to obtain a solder resist dry film resin composition.
[0073] Table 1 Formulation of solder resist dry film resin composition
[0074]
[0075] Application Example 2
[0076] This application example provides an application of the tetrafunctional alicyclic epoxy compound prepared in Example 2 in the preparation of a solder resist dry film resin composition, comprising the following steps:
[0077] According to the formula of the solder resist dry film resin composition shown in Table 2, the alkali-soluble resin, the photosensitive monomer, the photoinitiator, the thermosetting resin, the thermosetting catalyst, the additive and the solvent are uniformly mixed to obtain the solder resist dry film resin composition.
[0078] Table 2 Formulation of solder resist dry film resin composition
[0079]
[0080]
[0081] Comparative Example 1
[0082] This comparative example provides a method for preparing a solder resist dry film resin composition, comprising the following steps:
[0083] According to the formula of the solder resist dry film resin composition shown in Table 3, the alkali-soluble resin, the photosensitive monomer, the photoinitiator, the thermosetting resin, the thermosetting catalyst, the additive and the solvent are uniformly mixed to obtain the solder resist dry film resin composition.
[0084] Table 3 Formulation of solder resist dry film resin composition
[0085]
[0086] Experimental example
[0087] In this experimental example, the solder resist dry film resin compositions prepared in Application Example 1, Application Example 2 and Comparative Example 1 were subjected to performance tests to evaluate the comprehensive performance of the solder resist dry film of the present invention.
[0088] 1. Pre-treatment
[0089] (1) Preparation of photosensitive dry film: coating the mixed solder resist dry film resin composition on the surface of a PET support film with a thickness of 25 μm by a coating machine to obtain a photosensitive layer with a thickness of 25 μm, and covering the surface of the photosensitive layer with a PE protective film with a thickness of 25 μm;
[0090] (2) Laminating: The copper surface of the copper clad laminate is polished with a grinder, washed with water, and dried to obtain a bright and fresh copper surface, the PE protective film is peeled off, and the solder resist dry film resin composition is pasted on the copper clad laminate using a laminating machine, and then placed in an oven at 100° C. for 5 min;
[0091] (3) Exposure: The test substrate obtained after film lamination was left to stand for 15 minutes, and then exposed using a laser direct imaging (LDI) exposure machine with a wavelength of 365 nm. Then, the photosensitivity test was performed using a stouffer 41-step exposure ruler. The number of exposure grids was controlled at 14-20 grids, and the exposure energy was 8-20 mJ / cm 2 ;
[0092] (4) Development: After exposure, the sample was allowed to stand for 20 min, the PET support film was peeled off, and the sample was developed using an alkali developer. A 1% Na2CO3 aqueous solution was evenly sprayed onto the surface of the sample at 30°C for twice the development time (60 s). After development, the sample was washed with water and dried to obtain a substrate with a dry solder mask for evaluation.
[0093] 2. Performance Test
[0094] (1) Sensitivity evaluation
[0095] A Stouffer 41-level step exposure scale was placed on the test substrate obtained after the above film lamination to conduct a sensitivity test. After exposure and development, a solder resist dry film obtained by curing the solder resist dry film resin composition was formed on the surface of the test substrate. The exposure energy (mJ / cm 2 ), the sensitivity of the photosensitive resin composition was evaluated, and the smaller the value, the better the sensitivity.
[0096] (2) Resolution evaluation
[0097] Exposure is performed using a mask having a wiring pattern with a width of 1:1 between the exposed part and the unexposed part. After development for twice the minimum development time, the minimum mask width at which a cured resist line is normally formed is taken as the resolution value and observation is performed using a two-dimensional imager or a scanning electron microscope (SEM).
[0098] (3) Adhesion evaluation
[0099] On the test substrate obtained after the above film lamination, the photomask data of the wiring pattern with L / S=n:400 (unit: μm) was used to expose the energy so that the number of residual stages after development of the Stouffer 41-stage exposure ruler reached 20. After the development process, the resist pattern was observed using an optical microscope, and the adhesion (μm) was evaluated by taking the minimum line width of the complete cured resist line as the adhesion value. The smaller the value, the better the adhesion.
[0100] (4) Hardness evaluation
[0101] The hardness of the solder resist dry film obtained after pretreatment is measured according to the test method of GB / T1730-93.
[0102] (5) Viscosity evaluation
[0103] The viscosity of the solder resist dry film resin compositions of Application Example 1, Application Example 2 and Comparative Example 1 was measured respectively according to the test method of GB / T10247-2008.
[0104] (6) Chemical resistance evaluation
[0105] Acid and alkali resistance test: The prepared solder resist dry film was immersed in 5% H2SO4 solution at 50℃, 5% NaOH solution at 50℃, and 5% NaCl solution at 50℃ respectively for 30 minutes. The qualified standard is that there is no obvious change on the surface of the sample (such as no falling off or blistering).
[0106] (7) Flexibility evaluation
[0107] After lamination, exposure and development, the prepared solder mask dry film was folded 20 times from different angles to observe whether the dry film was cracked. The number of folding times when the dry film was cracked was counted. The larger the value, the better the flexibility of the dry film.
[0108] 3. Test Results
[0109] The above-mentioned properties of the solder resist dry film resin compositions prepared in Application Example 1, Application Example 2 and Comparative Example 1 were tested, and the test results are shown in Table 4.
[0110] Table 4 Performance test results of solder resist dry film resin composition
[0111] Application Example 1 Application Example 2 Comparative Example 1 <![CDATA[Exposure (mJ / cm 2 )]]> 25 25 27 Resolution(μm) 36 36 40 Adhesion(μm) 32 32 42 hardness 6H 6H 4H Viscosity (cps / 25℃) 16 16 28 Chemical resistance qualified qualified qualified Flexibility Cracking after 18 times Cracking after 18 times Cracking after 8 times
[0112] As can be seen from Table 4, the solder resist dry film resin composition prepared by using the tetrafunctional alicyclic epoxy compound of the present invention as a thermosetting resin is qualified in the chemical resistance test, and the test results of sensitivity and resolution are close to those of the solder resist dry film resin composition prepared by using ERL-4221 as a thermosetting resin, indicating that the solder resist dry film composition of the present invention can be used to prepare a solder resist dry film. Compared with the solder resist dry film prepared by using ERL-4221 as a thermosetting resin, the solder resist dry film of the present invention has slightly weaker test results in adhesion and viscosity, but the hardness and flexibility are significantly improved, the hardness evaluation result is 6H, and the dry film in the flexibility test cracks only after being folded in half 18 times. The above results show that the solder resist dry film prepared by the tetrafunctional alicyclic epoxy compound of the present invention has acid and alkali resistance, and is close to the solder resist dry film resin composition prepared by using ERL-4221 as a thermosetting resin in terms of sensitivity, resolution, adhesion, etc., and more effectively improves the hardness and flexibility of the solder resist dry film, so that it has better flexibility and hardness.
[0113] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. Application of tetrafunctional alicyclic epoxy compounds in the preparation of solder resist dry film, wherein: The structural formula of the tetrafunctional alicyclic epoxy compound is shown in formula (I):
2. The use according to claim 1, characterized in that: The solder resist dry film prepared from the tetrafunctional alicyclic epoxy compound is used for UV encapsulation and coating protection in at least one of optical display, electronic manufacturing, flat panel and flexible display devices.
3. The use according to claim 1, characterized in that: The application is the application of the tetrafunctional alicyclic epoxy compound in the preparation of a solder resist dry film resin composition, and the solder resist dry film resin composition is obtained by mixing the following raw materials in percentage by mass: 45% to 55% alkali-soluble resin, 10% to 15% photosensitive monomer, 3% to 4% photoinitiator, 15% to 20% of the tetrafunctional alicyclic epoxy compound, 0.5% to 1.5% thermal curing catalyst, 0.5% to 1.5% defoaming agent, 0.5% to 1.5% leveling agent and 15 to 20% solvent.
4. The use according to claim 3, characterized in that: The molecular structure of the alkali-soluble resin contains at least one of carboxyl and sulfonic acid groups, the weight average molecular weight of the alkali-soluble resin is 6000-9000, the acid value of the alkali-soluble resin is 40-120 mgKOH / g, and the solid content of the alkali-soluble resin is 40-50%.
5. The use according to claim 3, characterized in that: The photosensitive monomer is pentaerythritol triacrylate, the photoinitiator is diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, the thermal curing catalyst is 2-methylimidazole, the leveling agent is polyacrylate, the defoamer is a silane copolymer defoamer, and the solvent is acetone.
6. The use according to claim 3, characterized in that: The method for using the solder resist dry film resin composition comprises the following steps: Using a coating machine to coat a solder resist dry film resin composition with a thickness of 20 to 30 μm on the surface of a PET support film with a thickness of 20 to 30 μm to obtain a photosensitive layer, and covering the surface of the photosensitive layer with a PE protective film with a thickness of 20 to 30 μm; The PE protective film is peeled off, and the solder resist dry film resin composition is attached to the surface of the electronic component. After baking at 90-110° C. for 3-10 minutes, it is allowed to stand for 10-20 minutes. Then, the circuit board is exposed with a laser having a wavelength of 300-400 nm, and then it is allowed to stand for 15-30 minutes. The PET supporting film is peeled off, the electronic component is developed, and then the electronic component is washed and dried to obtain the solder resist dry film attached to the electronic component.
7. The use according to any one of claims 1 to 3, characterized in that: The preparation method of the tetrafunctional alicyclic epoxy compound comprises the following steps: S1, pentaerythritol, 3-cyclohexene-1-carboxylic acid, a catalyst and an organic solvent are mixed to obtain a solid-liquid mixture, a condensing agent is dissolved in an organic solvent to obtain a first mixed solution, the first mixed solution is added dropwise to the solid-liquid mixture, and the mixture is stirred and reacted for 16 to 24 hours, the reaction system after the reaction is washed and dried to obtain an organic phase, and the organic phase is distilled under reduced pressure, and the residue of the organic phase obtained by the distillation under reduced pressure is crystallized to obtain pentaerythritol tetracyclohexene carboxylate; S2, dissolving pentaerythritol tetracyclohexene carboxylate in an organic solvent to obtain a second mixed solution, dissolving meta-chloroperbenzoic acid in an organic solvent to obtain a third mixed solution, then dropping the third mixed solution into the second mixed solution under ice bath conditions, stirring and reacting for 16 to 24 hours, filtering, purifying the filtered filtrate to obtain an organic phase, and crystallizing to obtain a tetrafunctional alicyclic epoxy compound; The catalyst is selected from at least one of 4-dimethylaminopyridine, 1-hydroxybenzotriazole, and 4-pyrrolidinopyridine; the condensing agent is selected from at least one of N,N-dicyclohexylcarbodiimide, N,N-diisopropylcarbodiimide, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide; and the organic solvent is selected from at least one of tetrahydrofuran and dichloromethane.
8. The use according to claim 7, characterized in that: The molar ratio of the pentaerythritol, 3-cyclohexene-1-carboxylic acid, catalyst and condensation agent is 1:(4-4.12):(1-1.10):(4-4.10), and the molar ratio of the pentaerythritol tetracyclohexene carboxylate to meta-chloroperbenzoic acid is 1:(4-4.10).
9. The use according to claim 7, characterized in that: In step S1, the washing treatment method is to transfer the reaction system after the reaction to a separatory funnel, add an organic solvent to the separatory funnel, wash it three times with a 1% hydrochloric acid solution, and then wash it three times with a saturated sodium chloride solution, and separate the liquids to obtain a lower organic phase; Alternatively, the reaction system after the reaction is transferred to a separatory funnel, 10 to 50 mL of an organic solvent is added to the separatory funnel, and the mixture is first washed three times with a 1% hydrochloric acid solution, then washed three times with a saturated sodium bicarbonate solution, and then washed three times with a saturated sodium chloride solution, and the lower organic phase is obtained by separation; Alternatively, the reaction system after the reaction is transferred to a separatory funnel, 10 to 50 mL of an organic solvent is added to the separatory funnel, the organic phase is washed three times with a 1% by mass hydrochloric acid solution, and the lower organic phase is obtained by separation.
10. The use according to claim 7, characterized in that: In step S1, the method of drying the reaction system after the reaction to obtain the organic phase is to add a solid desiccant to the washed reaction system, filter and retain the organic phase; In step S2, the purification treatment method is to first add a saturated sodium sulfite solution to the filtrate, then wash the filtrate with a saturated sodium bicarbonate solution and a saturated sodium chloride solution for three times, separate the liquids to obtain a lower organic phase, add a solid desiccant to the washed organic phase, and then remove the organic solvent in the organic phase by reduced pressure distillation; The conditions of the reduced pressure distillation are: the filtered organic phase is distilled under reduced pressure for 1 to 3 hours at a vacuum degree of -0.098 MPa and a water bath temperature of 30 to 40°C.
Citation Information
Patent Citations
Photosensitive resin composition, cured product, and image display device
CN118489087A
Curable composition
CN101346415A
Multifunctional alicyclic epoxy monomer as well as preparation method and application thereof
CN118852065A
Solidifiable compositions
CN1296047A
Multilayer printed wiring board and insulating resin composition used therefor
JP2001135939A